Kepuasan Pasien BPJS Ditinjau Dari Nomor Antrian Pendafataran Rawat Jalan Rumah Sakit Umum Darmayu Ponorogo - Kusuma Putri Rahayu; Ani Rosita; Dwi Nurjayanti (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2019)
Patient satisfaction is the patient's feelings about the performance of the officers in health services in accordance with the level of expectations. The purpose of this study was to determine the satisfaction of BPJS patients in terms of the queue number in the outpatient registration of Darmayu Hospital Ponorogo. This research design is descriptive qualitative. The study population was 50 BPJS patients. The sample was selected by accidental sampling technique. Data were collected through filling out a questionnaire, then analyzed descriptively. Most respondents got a queue number as much as 96% (48 respondents) and respondents who did not get a queue number were 4% (2 respondents). A total of 34 respondents (68%) were satisfied with the registration service according to the queue number, as many as 32% (16 respondents) were very satisfied, while patients who were quite satisfied and unsatisfied were not there (0%). It is recommended that the queue number be given when a new patient arrives by providing a fixed flow and procedure so that it is easier for the patient to get registration services, especially regarding the queue number, as well as the continuous application of SIM-RS in registration services. Keywords: TPPRJ; patient satisfaction; BPJS ABSTRAK Kepuasan pasien merupakan perasaan pasien terhadap kinerja petugas di pelayanan kesehatan sesuai dengan tingkat harapannya. Tujuan penelitian ini adalah untuk mengetahui kepuasan pasien BPJS ditinjau dari nomor antrian di pendafataran rawat jalan RSU Darmayu Ponorogo. Desain penelitian ini adalah deskriptif kualitatif. Populasi penelitian adalah pasien BPJS sejumlah 50 responden. Sampel dipilih dengan teknik accidental sampling. Data dikumpulkan melalui pengisian kuesioner, lalu dianalisis secara deskriptif. Sebagian besar responden mendapatkan nomor antrian sebanyak 96% (48 responden) dan responden yang tidak mendapatkan nomor antrian sebanyak 4% (2 responden). Sejumlah 34 responden (68%) puas dengan pelayanan pendaftaran sesuai nomor antrian, sebanyak 32% (16 responden) adalah sangat puas, sedangkan pasien yang cukup puas dan kurang puas adalah tidak ada (0%). Disarankan agar nomor antrian diberikan pada saat pasien baru datang dengan memberikan alur dan prosedur yang tetap agar pasien menjadi lebih mudah mendapatkan pelayanan pendafataran, kususnya tentang nomor antrian, serta diterapkannya SIM-RS yang berkesinambungan di pelayanan pendaftaran. Kata kunci: TPPRJ; kepuasan pasien; BPJS